Financial Liquidity of the Horticultural Enterprise PPO Siechnice in Poland - Kropsz, Irena (Equilibrium. Equilibrium. Quarterly Journal of Economics and Economic Policy, 2010)
One of the key issues in evaluating the financial condition of a company is the analysis of assets in relation to the due indebtedness, i.e., short-term obligations. Liquidity ratios calculated in such a manner help in the drawing of conclusions on the liquidity of the enterprise and its ability to pay its short-term liabilities. This paper examines the financial liquidity in 2005-2007 of a horticultural enterprise, producing and selling food, based on information available in the balance sheet, income statement, and the cash flow statement, as published in the company’s financial reports. The company was selected using the following criteria: location in Lower Silesia, Poland, in a municipal-rural commune, and operating in the agricultural-food sector. The study was based on business books of the examined company. The economic analysis involved mainly the financial liquidity ratios. Additionally, descriptive and comparative methods were used to characterize and interpret the results. The results of the study show that the company had a good financial situation and had no problems with payment of current obligations without waiting for accounts receivable or de-stocking. Additionally, liquidity analysis based on transfers from its operating activity showed that the obligations of the examined company could be covered by money obtained during its operating activities.